If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 3x = -6x + 13x Combine like terms: -2x + 3x = 1x 1x = -6x + 13x Combine like terms: -6x + 13x = 7x 1x = 7x Solving 1x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 1x + -7x = 7x + -7x Combine like terms: 1x + -7x = -6x -6x = 7x + -7x Combine like terms: 7x + -7x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| 12/23*2/4*(11/12-5/18) | | 4x-7=-9x+84 | | 24x+38=14x | | 5v+9=33 | | 42/7a | | (4x+1)(7x-6)=0 | | 5x^2-7+2=0 | | 9x+1=3x+31 | | (2x+4)*(x-1)-36=0 | | 180x^4-108x^3-107x^2+36x+20=0sol | | 4x=46-10 | | 3(2x+1)+5=7-3x | | 9x-7=-2x+-40 | | 4/5c•4c/18 | | 7x-8=9x+(2) | | Ln(2.5x)=3 | | 13x-66=90 | | 3x+5y-7x=37findx | | y^2+2y+x^2-24=14 | | 9x+2=7x+-14 | | 10x-20=7x+10 | | 6x+56+10=180 | | 0.9/COS | | 5(3x+5)=4(3x+4)+3 | | -5(5-x)+4=3(x-1) | | (-2x)/(12x) | | 2(3x+5)=4(x-5)+2x | | -2x/12x | | 6x+3=-3x+-60 | | 4(2x-2)=3(5x-3) | | -2b+8=-15 | | -198=-18x |